2023
DOI: 10.3390/medicina59030638
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nutrition in the Etiopathogenesis and Prevention of Nonalcoholic Fatty Liver Disease (NAFLD) in a Group of Obese Adults

Abstract: Nonalcoholic fatty liver disease (NAFLD) is liver damage characterized by an accumulation of triglycerides in hepatocytes of >5% (due to an alteration of the balance of the lipid metabolism in favour of lipogenesis compared to lipolysis) that is not induced by the consumption of alcohol. The pathology includes simple steatosis and nonalcoholic steatohepatitis, or NASH (steatosis associated with microinflammatory activities), which can evolve in 15% of subjects with hepatic fibrosis to cirrhosis and the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…The subjects of this study decreased their depressive symptoms after 6, 12, and 24 months of dietary intervention, aligned with the improvement in glucose levels and the reduction in body composition variables. Several studies showed a reduction in depressive symptoms after following a balanced dietary intervention [ 63 ], sustained physical activity, and adherence to the MedDiet [ 64 ]. In addition, changes in depressive symptoms were related to an improvement in HDL-c and adiponectin, which are related to MASLD.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects of this study decreased their depressive symptoms after 6, 12, and 24 months of dietary intervention, aligned with the improvement in glucose levels and the reduction in body composition variables. Several studies showed a reduction in depressive symptoms after following a balanced dietary intervention [ 63 ], sustained physical activity, and adherence to the MedDiet [ 64 ]. In addition, changes in depressive symptoms were related to an improvement in HDL-c and adiponectin, which are related to MASLD.…”
Section: Discussionmentioning
confidence: 99%